Increasing Students’ Interest in Learning Mathematics Using the Make a Match Learning Method in Grade V Elementary School - Amiruddin Amiruddin; Annisa Aulia Hutasuhut; Haniatul Khoiriyah; Shinta Apriani; Siti Qomariah Dalimunte; Sri Ayuni Asih (Edumaspul: Jurnal Pendidikan, 2022)
This study uses qualitative research methods, by using qualitative research methods researchers are easier to conduct research by observing students who are the object of research. Researchers also make a match learning method is one method that can be used in the application of a lesson, using this method involves students working actively, because the make a match method is a method that motivates all students to be active and provides opportunities for students to think , are free to express opinions according to the thoughts they get. With this method, it can be seen that the use of this method greatly influences the development of students who are more active in carrying out learning.